A high-throughput gene expression analysis technique using competitive PCR and matrix-assisted laser desorption ionization time-of-flight MS - Ding, Chunming (The National Academy of Sciences, 2003)
We report here an approach for gene expression analysis by combining competitive PCR and matrix-assisted laser desorption ionization time-of-flight MS. A DNA standard is designed with an artificial single nucleotide polymorphism in the gene of interest. The standard is added to the reverse transcription product before PCR. Subsequently, a base extension reaction is carried out at the single nucleotide polymorphism position, and the products are quantified by matrix-assisted laser desorption ionization time-of-flight MS. The approach is capable of relative and absolute quantification of gene expression; it is extremely sensitive (as few as five copies of DNA were quantified) and highly reproducible. It is also capable of simultaneous quantification of both alleles for heterozygotes and alternatively spliced genes. We have incorporated this technique with the homogeneous Mass Extension system (Sequenom) to create a high-throughput, automated gene expression analysis platform where a few hundred genes from 20–500 different samples can be accurately quantified per day.